2020
DOI: 10.1002/suco.201900418
|View full text |Cite
|
Sign up to set email alerts
|

Influence of long‐term creep on prestressed concrete beams in relation to deformations and structural resistance: Experiments and modeling

Abstract: Realistic structural models incorporating the time‐dependent effects of concrete are essential in order to make accurate predictions of the time‐dependent deflections at any time of the service life. Experimental databases are used to calibrate and validate existing models for creep and shrinkage available in international standards. However, extensive research campaigns on large‐scale prestressed beams are scarce. In 1967–1985, a research program comprising a unique set of long‐term experimental data on concr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Prestressed concrete beams having parabolic tendons were tested by Reybrouck et al 20 for a period of 4.5 years. Ten beams having an I‐shaped cross‐section and six beams with rectangular cross‐section were tested under a sustained load applied using the four‐point loading setup having 40 MPa cube strength.…”
Section: Introductionmentioning
confidence: 99%
“…Prestressed concrete beams having parabolic tendons were tested by Reybrouck et al 20 for a period of 4.5 years. Ten beams having an I‐shaped cross‐section and six beams with rectangular cross‐section were tested under a sustained load applied using the four‐point loading setup having 40 MPa cube strength.…”
Section: Introductionmentioning
confidence: 99%
“…This paper provides a concise review of the concrete creep studies in compression, tension and flexure of plain concrete reported in literature. Studies on plain concrete subject to bending in literature are limited as most of the recent research is focussed on bending creep in reinforced concrete [1][2][3] and prestressed concrete [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Since the 1960s, pre‐stressed concrete (PC) members have been used in building structures and infrastructure facilities due to their advantages such as higher quality, more economic efficiency, a shorter span of construction, and more durable aesthetics 38,39 . A glance at the history of using the post‐tensioning as a type of pre‐stressing in composite sections shows that post‐tensioning the concrete core of composite sections has been used for the first time in the construction of the arch bridge in Aurora 40,41 …”
Section: Introductionmentioning
confidence: 99%
“…38,39 A glance at the history of using the post-tensioning as a type of pre-stressing in composite sections shows that post-tensioning the concrete core of composite sections has been used for the first time in the construction of the arch bridge in Aurora. 40,41 Wang et al 42 studied the axial behavior (compressive and tensile) and the design of hot-finished high-strength steel tubular elements with internal pre-stressed cables experimentally and numerically and used verified numerical models for these elements under compression to conduct a parametric study of their behavior. Their study showed that the presence of the cables enhanced the tensile capacity of the members while the addition of prestress extended the elastic range.…”
Section: Introductionmentioning
confidence: 99%